Ecological approaches to environmental law - Bosselmann, Klaus, 1951-; Taylor, Prue, 1961- (International library of law and the environment, 2017)
This research review offers a comprehensive discussion of a kaleidoscope of articles that cover ecological approaches into environmental law. It looks at the critique of environmental law, the ethical dimensions, and methodology before exploring the key issues focusing on rights and responsibilities, property and the commons, governance and constitutionalism. It also discusses articles on the theory of Earth Jurisprudence. Written by two leading academics in this area, this research review is an indispensable reference for anyone concerned with ecological approaches to environmental law.